Eleven Danish patients diagnosed with Scabies and treated with Tenutex®. Issue 3 (2nd February 2021) - Soerensen, Christian A. S.; Pallesen, Kristine Appel Uldall; Munk, Nadja Trier; Vestergaard, Christian
Abstract: Treatment with Tenutex ® should be considered in patients diagnosed with scabies if the first‐line treatment with 5% permethrin fails. Treatment failure with 5% permethrin may be due to tolerance or resistance in scabies mites. Abstract : Treatment with Tenutex ® should be considered in patients diagnosed with scabies if the first‐line treatment with 5% permethrin fails. Treatment failure with 5% permethrin may be due to tolerance or resistance in scabies mites.